MOTORIČKE SPOSOBNOSTI UČENICA PRVOG, DRUGOG I TREĆEG RAZREDA OSNOVNE ŠKOLE - Nevenka Zrnzević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The aim of this research was to establish the motor abilities of female students from the fi rst, second and third grade of primary school. 254 female students from the primary schools in Trstenik were tested for the research. Motor abilities were estimated according to seven variables (agility on the fl oor, forward bend on a bench, long jump from standing start, 30 m dash from a fl ying start, 300 m run, the throwing of medicine ball, keeping in pull-up position). The differences between female students of primary school were estimated according to the multivariant analysis of variance. The results of the research showed that, viewing from the aspect of motor abilities, there are differences between female students from the fi rst, second and third grade of primary school and they are statistically signifi cant.